Development Model of Restorative Justice by Participation of Community - Narinth , Nat; Tritrungtreekoon, Jrinptip (Community and Social Development Journal, 2020)
This research has objectives for study and develop model of restorative justice by participation of community. To study operation model of community justice Mae Tuen sub-district, Omkoi district, Chiang Mai province in management of problems that affect community of 4 villages are Ban Mai , Ban Huay Lor Dook, Ban Huay Dee Mor and Ban Mae Tuen Noi. In order that, has qualitative research included studying current condition problems and model of restorative justice by field survey, conference with community to bring knowledge for evaluation in develop model of restorative justice. The results revealed that community has drug problem, affray problem, land benefit problem and debt problem. Which community justice Mae Tuen sub-district initially cannot use model of restorative justice by participation of community for problems management because of commissioner lack of understanding in the role to operation, lack of systematic management, lack of public relations to community. Researchers have to bring the problems for solving process by community. Found that each village has model for solving problems by conciliation under sub-district headman, village headman, community leader to be the main part with community, village rules, methods to reimburse the offense, restoring relations for solving problems by themselves. That community justice Mae Tuen sub-district can take the results to develop operation model. However, should be support from central authority for develop skills, knowledge and evaluate the guideline to give community justice Mae Tuen sub-district can provide justice for community.